Massage with aromatherapy: effectiveness on anxiety of users with personality disorders in psychiatric hospitalization - Domingos, Thiago da Silva [UNESP]; Braga, Eliana Mara [UNESP] (Univ Sao Paolo, 2015)
Objective: To investigate the effectiveness of aromatherapy massage using the essential oils (0.5%) of Lavandula angustifolia and Pelargonium graveolens for anxiety reduction in patients with personality disorders during psychiatric hospitalization. Method: Uncontrolled clinical trial with 50 subjects submitted to six massages with aromatherapy, performed on alternate days, on the cervical and the posterior thoracic regions. Vital data (heart and respiratory rate) were collected before and after each session and an anxiety scale (Trait Anxiety Inventory-State) was applied at the beginning and end of the intervention. The results were statistically analyzed with the chi square test and paired t test. Results: There was a statistically significant decrease (p < 0.001) of the heart and respiratory mean rates after each intervention session, as well as in the inventory score. Conclusion: Aromatherapy has demonstrated effectiveness in anxiety relief, considering the decrease of heart and respiratory rates in patients diagnosed with personality disorders during psychiatric hospitalization.
Keywords: Personality Disorders; Anxiety; Massage; Aromaterapy; Complementary Therapies; Psychiatric Nursing